Administrative and technical obstacles of school principals in the Directorate of Education in the North Western Badia District and their proposals to address them - Shawaqfeh, Afaf Nasser Sauh (Journal of Educational and Psychological Sciences, 2022)
The study aimed to identify the reality of administrative and technical obstacles to school principals in the Directorate of Education for the North West Badia and their suggestions to address them and to achieve the objectives of the study, the descriptive approach was used, and the tool was a survey of (35) paragraph, which has been distributed to a sample 130) principal ; The results showed that the degree of obstacles on the community as a whole had an average (4.16 of 5) and at the field of areas; The fields on students received at the top of the average (4.41) and the constraints of the technological equipment for the school at average (4.39) and the obstacles to the implementation of the curriculum at an average (4.25) and all of which is a verbal estimate (very large); Constraints relating to the local community (3.97) and fifth; Constraints on teachers with average (3.76) and two of the last two verbal assessment (large), and the results have no statistically significant differences at a significant level (0.05 = α) is attributed to the impact of gender in all areas and in total level, except for the constraints of teachers and the differences in favor of male, There are statistically significant differences for the impact of scientific qualifications in all fields. According to the results, the researcher recommended the participation of staff and entities in the face of administrative and technical constraints through the use of their views, to find ways to facilitate and overcome them.